IMPLEMENTASI KEBIJAKAN PERLINDUNGAN ANAK DI KOTA BANDUNG - Ihsanul Farhan (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2022)
This research explains how the implementation of the Child Protection Policy in UPTP2TP2a Bandung City. The research method used is a qualitative approach using data collection techniques with in-depth interviews, observation, documentation, and literature studies. The results of the study revealed that the implementation of the child's protection policy by UPT P2TP2A Bandung City was still not optimal. All cases of victims reported can be completed according to child protection procedures, but stabilization of performance is still needed. Therefore, to streamline the implementation of children's judicial procedures both victims and children, doors must open time efficiency and fast service in accordance with the criminal justice system.